1993
DOI: 10.1007/bf01150476
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protein kinase C in rat and human prostates

Abstract: The properties of protein kinase C (PKC) activity have been studied in cytosolic and membrane fractions from rat and human prostate. Ion exchange chromatography indicated the existence of different PKC isoforms, PKC from rat ventral prostate behaved as a classical Ca(2+)- and phospholipid-dependent enzyme and was activated by 1,2-diacylglycerol as well as by high concentrations of arachidonic acid. PKC activity in the cytosolic fraction was higher and presented different cofactor requirements than that in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Hence, E 2 may activate PKC activity in these cells by enhancing intracellular Ca 2ϩ . It should be noted that human BPH tissue reportedly contains TPA-but not Ca 2ϩ -activated PKC isoforms (25). Hence, in prostate epithelial cells, the effect of E 2 on melatonin receptors may be predominantly mediated by a PKC isoform(s) that is not directly regulated by Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, E 2 may activate PKC activity in these cells by enhancing intracellular Ca 2ϩ . It should be noted that human BPH tissue reportedly contains TPA-but not Ca 2ϩ -activated PKC isoforms (25). Hence, in prostate epithelial cells, the effect of E 2 on melatonin receptors may be predominantly mediated by a PKC isoform(s) that is not directly regulated by Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PKC by androgens has also been reported in some studies (22), but not in others (23,24). Human BPH tissue has been reported to contain phospholipid-dependent, phorbol 12-myristate 13-acetate (TPA)-activated, PKC isoforms (25). Hence, in the present study we investigated the possibility that the effects of E 2 on melatonin receptors and responses in prostate epithelial cells were mediated by PKC.…”
mentioning
confidence: 93%
“…Regarding isoforms being involved in PKCmediated contractions, previous publications using cultured stromal cells provided controversial findings. Thus, it has not only been reported that PKC activity in human tissues was calcium-independent (i.e., not imparted by PKCα, -β, or -γ) 41 but also that contractions by PKC-activating phorbol esters were susceptible to calcium channel blockers. 15 As our detection by RT-PCR was semiquantitative and based on isoform-specific primers, conclusive comparisons of expression levels cannot be performed between the different isoforms.…”
Section: Effects Of Gf109203x and Go6983 In The Presence Of L-name And Diclofenacmentioning
confidence: 99%